Negotiating racial politics in the family : transnational histories touched by National Socialism and Apartheid - Henkes, Barbara (Egodocuments and history series, 2020)
"This book is situated at the cutting edge of the political-ethical dimension of history writing. Henkes investigates various responsibilities and loyalties towards family and nation, as well as other major ethical obligations towards society and humanity when historical subjects have to deal with a repressive political regime. In the first section we follow three pre-war German immigrants in the Netherlands during the era of National Socialism. The second section explores the positions of three Dutch post-war emigrants who left for South Africa. The narratives of these transnational agents and their relatives provide a lens through which changing constructions of national identities, and the personal acceptance or rejection of a nationalist policy on racial grounds, can be observed in everyday practice"--